REVISION OF THE BRACHIOPOD FAMILY SCHRENKIELLIDAE LAZAREV, 1990 - Lazarev S.S. (My University, 2004)
Problems of the morphology, evolution, and systematics of the brachiopod family Schrenkiellidae are discussed. A new subfamily, Coopericinae, and a new genus, Coopericus, are established. New genera Krekarpius and Elalia, with the type species E. aljutovensis sp. nov., are described in the subfamily Schrenkiellinae from the stratotype section of the Aljutovo Formation of the Moscow Basin.